2003
DOI: 10.1677/joe.0.1790073
|View full text |Cite
|
Sign up to set email alerts
|

Frequent overexpression of cyclin D1 in sporadic pancreatic endocrine tumours

Abstract: Pancreatic endocrine tumours (PETs) occur sporadically or are inherited as part of the multiple endocrine neoplasia type-1 syndrome. Little is known about the molecular events leading to these tumours. Cyclin D1, a key regulator of the G1/S transition of the cell cycle, is overexpressed in a variety of human cancers as well as certain endocrine tumours. We hypothesized that similar to other endocrine tumours, cyclin D1 is overexpressed in human sporadic PETs. Cyclin D1 protein overexpression was found in 20 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
3
39
0
2
Order By: Relevance
“…7 However, the evidence for a relationship between solid pseudopapillary neoplasms and neuroendocrine tumors also ends here, since solid pseudopapillary neoplasms have never been found to express other essential neuroendocrine features such as chromogranin A, peptide hormones 7 or neurosecretory granules. 29 We also were unable to confirm the reported frequent upregulation of cyclin D1 expression in pancreatic neuroendocrine tumors 30,31 on the basis of our data. In our series, we found that cyclin D1 expression is rare in pancreatic neuroendocrine tumors in contrast to solid pseudopapillary neoplasms.…”
Section: Discussionmentioning
confidence: 59%
“…7 However, the evidence for a relationship between solid pseudopapillary neoplasms and neuroendocrine tumors also ends here, since solid pseudopapillary neoplasms have never been found to express other essential neuroendocrine features such as chromogranin A, peptide hormones 7 or neurosecretory granules. 29 We also were unable to confirm the reported frequent upregulation of cyclin D1 expression in pancreatic neuroendocrine tumors 30,31 on the basis of our data. In our series, we found that cyclin D1 expression is rare in pancreatic neuroendocrine tumors in contrast to solid pseudopapillary neoplasms.…”
Section: Discussionmentioning
confidence: 59%
“…Although our understanding of the cellular biology and clinical behavior of NETs has increased in sophistication, insights into their underlying molecular genetics have lagged behind. A number of candidate genes have been implicated in the pathogenesis of PNETs (reviewed in (Duerr & Chung 2007)), including multiple endocrine neoplasia type 1 (MEN1; Shan et al 1998, Wang et al 1998, retinoic acid receptor-b (House et al 2003b), hMLH1 (human mutL homologue 1; House et al 2003a), RASSF1 (Ras association domain family 1; House et al 2003b), Her2/neu (herstatin; Evers et al 1994, Goebel et al 2002, and the cell cycle regulators cyclin D1 (Chung et al 2000, Guo et al 2003 INK4a /p14 ARF (Muscarella et al 1998), p18 INK4c , and p27…”
Section: Introductionmentioning
confidence: 99%
“…In these particular tumors, the relation between menin expression and cyclin D1 or NF-kB activity is not well documented. Overexpression of cyclin D1 frequently occurs in pancreatic endocrine tumors (Chung et al, 2000;Guo et al, 2003) or in parathyroid adenomas (Mallya et al, 2000), and this overexpression has been postulated to be an early event in neuroendocrine tumorigenesis (Chung, 2004). Parathyroid tumorigenesis is dependent on both cyclin D1 and menin (Rosenberg et al, 1991;Bhuiyan et al, 2000) and parathyroid hyperplasia is induced by an overexpression of cyclin D1 or a loss of menin function in transgenic mice (Imanishi et al, 2001;Bertolino et al, 2003;Libutti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%